DINAMIKA DAN EKSISTENSI HUKUM ISLAM DI INDONESIA (Lex Jurnalica, 2017)
AbstractThe dynamics of Islamic law in Indonesia is a portrait of a dialectic of Muslims in Indonesia in the face of his day. The contribution of Islamic law in the legal system construction in Indonesia is quite in line with the growing challenges of an increasingly complex legal problems in accordance with the times. The new issue has never been found in the books of the law written by the mujtahid earlier so that the scholars interpret the Islamic law back in for more actual and can respond to the challenges of the times, with the development of the benefit of the community. The effort known as the implementation of Islamic law. The construction of the law can be formulated as a continuous process and don't know the end of Nations as Indonesia with regard to how the law is planned, formed, formulated, implemented, enforced, and institutionalized. The legal system of Indonesia, as a result of historical development are compounds. Called so because until now in the Republic of Indonesia applicable some legal systems have the pattern and arrangement of its own. That question is the system of customary law, Islamic legal system and the legal system of the West. Three systems of law that took effect in Indonesia at the time. Islamic law has existed on the islands of Indonesia since Muslims came and settled in this archipelago.Keywords: Islamic law, dynamics of Islam, the application of the lawÂ AbstrakDinamika Hukum Islam di Indonesia merupakan potret dialektika umat Islam di Indonesia dalam menghadapi zamannya. Kontribusi hukum Islam dalam sistem pembinaan hukum di Indonesia cukup berkembangan sejalan dengan tantangan problematika hukum yang semakin kompleks sesuai dengan perkembangan zaman. Persoalan baru tersebut belum pernah ditemukan dalam kitab-kitab hukum yang ditulis oleh para mujtahid terdahulu sehingga para ulama menginterpretasikan kembali agar hukum Islam tersebut lebih aktual dan dapat menjawab tantangan dari perkembangan zaman, dengan perkembangan kemaslahatan masyarakat. Usaha tersebut dikenal dengan reaktualisasi hukum Islam. Pembangunan hukum dapat dirumuskan sebagai proses yang berkesinambungan dan tidak kenal akhir sebagai upaya segenap bangsa Indonesia berkenaan dengan cara hukum itu direncanakan, dibentuk, dirumuskan, diterapkan, ditegakkan, dan dilembagakan. Sistem hukum Indonesia, sebagai akibat dari perkembangan sejarahnya bersifat majemuk. Disebut demikian karena sampai sekarang di dalam negara Republik Indonesia berlaku beberapa sistem hukum yang mempunyai corak dan susunan sendiri. Yang dimaksud adalah sistem hukum adat, sistem hukum Islam dan sistem hukum Barat. Ketiga sistem hukum itu mulai berlaku di Indonesia pada waktu yang berlainan. Hukum Islam telah ada dikepulauan Indonesia sejak orang Islam datang dan bermukim di nusantara ini.Kata kunci : Hukum Islam, dinamika Islam, penerapan hukum, eksistensi